Analisis Effect Size Pengaruh Pembelajaran IPA Berbasis SETS Terhadap Kemampuan Proses Sains dan Hasil Belajar Peserta didik - Westi Widia Wati*; Asrizal Asrizal; Usmeldi Usmeldi (Universitas Syiah Kuala, 2022)
The competience of 21st century emphasizes to the skills, attitudes and knowledge. Science proses skills are skills that must be possessed by stuents in facing the challenges of the 21st century, an these skills also have a significants influence on student achievement, because science process skills are comprehensive and directed skills that cover the cognitive and psychomotor domains. The SETS approach in science learning is proven to be able to improve science process skills and student achievement. The purpose of this stuy is to find out the effect of the SETS approach in science learning on science process skills and student achievement. This type of research is a meta-analysis research. The sample use is 20 journals that have met the criteria. The data analysis technique is the calculation of the effect size of each journal. Based on the results of the study, it can be concluded that the SETS approach in science learning has a significants influence at every level of education an every grade level, both elementary and junior high schools in improving science prosess skills and student achievement.